(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
In this paper both synchronous and asynchronous buck-converter were designed to work in continuous conduction mode “CCM” and to deliver small load current. Then the two topologies were tested in terms of efficiency at small load current by use of different values of switching frequencies (range from 150 KHz to 1MHz) and three separated values of duty-cycle (0.4, 0.6 and 0.8). Obtained results turns out that efficiency of both synchronous and asynchronous buck-converter “switching step-down voltage regulator” responds in a negative manner to the increase in the switching frequency. However, this impact is being stronger in synchronous topology because of magnifying effect of losses related to switching frequency compared to those related to conduction when working at small load currents; this behavior makes obtained efficiency of both topologies in convergent levels when they operated to deliver small output current especially when working with higher switching frequencies. Larger duty-cycle can rise up the efficiency of both topologies.